Information seeking behaviour in music conductors’ repertoire selection - Christina Firkins; Michael Barrett-Berg; Ina Fourie (Information Research: An International Electronic Journal)
Introduction. Music repertoire selection is a process driven by music conductors. They focus on scoring, ensemble composition, acquisition methods (i.e., acquiring the music). Information needs and seeking are core to repertoire selection and conductors’ tasks/roles. It cannot be considered in isolation; other conductor responsibilities, past experiences, and external factors (e.g., finances) influence the process and information seeking. We report findings from an exploratory study conducted in 2023 with 37 conductors.